Effects of crab shell waste as feed on growth performance and colouration of siamese fighting fish (Betta splendens) - Connie Fay Komilus; Nurul Ashikin Mohamad-Zuki; Nur Hamna Aminudin; Aidil Ikhwan Redhwan; Nurul Aina Nadhirah Mohd-Khairulnizam (Penerbit Universiti Kebangsaan Malaysia, 2023)
Betta splendens, Siamese fighting fish exhibit behavior, coloration, and morphology that make them popular aquarium fish in aquaculture. Coloration for this fish requires high-quality feeds rich in carotenoids. Crab shells, mostly dumped as agro-waste by the seafood industry contain carotenoids and protein that can be an alternative for carotenoids in fish feed. The objectives of this study were to analyze the proximate composition and carotenoid content in feed and determine the effect of crab shells as feedstuff on the growth performance and coloration of Betta splendens. A 40-day feeding trial using 45 tails of B. splendens with an average body weight, of 0.25 g was conducted by using five feed treatments namely TC (0% crab shell), T1 (25% crab shell), T2 (50% crab shell), T3 (75% crab shell) and T4 (100% crab shell) respectively. Sampling was done weekly. Analysis done were proximate composition and extraction of carotenoid while growth performance parameters such as body weight gain (BWG), specific growth rate (SGR), feed intake (FI), and feed conversion ratio (FCR) were also taken. Skin coloration and water quality data were collected every 10 days. All data were analyzed using One-Way ANOVA via SPSS. Results showed protein content for T1 (22.40±0.29) was slightly higher compared to all treatments. Carotenoid content in crab shells was lower compared to krill. Body weight from T1 (25% crab shell) showed a significant increase among all treatments. All treatments show no changes in coloration. In conclusion, T1 (25% crab shell waste) is the best treatment as it has a high protein content that improves body weight gain without any significant effect on coloration in all treatments.